2020
DOI: 10.1111/andr.12941
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox transcription factor Meis1 is crucial to Sertoli cell mediated regulation of male fertility

Abstract: Background Infertility has become a global phenomenon and constantly declining sperm count in males in modern world pose a major threat to procreation of humans. Male fertility is critically dependent on proper functioning of testicular Sertoli cells. Defective Sertoli cell proliferation and/or impaired functional maturation may be one of the underlying causes of idiopathic male infertility. Using high‐throughput “omics” approach, we found binding sites for homeobox transcription factor MEIS1 on the promoters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…In addition, conditional knockout of RHOX10, an HD-harboring homeobox protein, causes spermatogenic defects and male infertility (21). Another homeobox gene, Meis1, is essential for Sertoli cell-mediated regulation of male fertility (22). Nevertheless, the function of HD proteins in fertility, especially those proteins mainly expressed in germ cells, remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, conditional knockout of RHOX10, an HD-harboring homeobox protein, causes spermatogenic defects and male infertility (21). Another homeobox gene, Meis1, is essential for Sertoli cell-mediated regulation of male fertility (22). Nevertheless, the function of HD proteins in fertility, especially those proteins mainly expressed in germ cells, remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was suggested that the expression of these genes may have the potential for predicting successful sperm retrieval. Another study evaluated the transcriptomic profile of testicular tissues derived from NOA and obstructive azoospermia (OA) men, in order to determine whether gene products from spermatogenic cells could be detected in the Sertolicell only testes (SCOT) [44]. Transcripts specific to immature germ cells such as UTF1, CD9, DDX4, EPCAM, GFRA1, KIT, LIN28, DMRT, GPR125, UCHL1, and NANOG were detected in 65% of SCOT, with 45% of SCOT showing positive immunoreactivity to DDX4 in the spermatogonia.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…The fertility assessment was done by measuring parameters like gonadosomatic index, sperm count, and litter size in the transgenic and age-matched wild-type mice. 53,[80][81][82] The body weight and testis weight for each mouse (WT or transgenic) was noted, and the gonadosomatic index (body weight/testis weight  100) was calculated. The testis size was also observed for any visible morphological changes.…”
Section: Fertility Assessmentmentioning
confidence: 99%